Measuring the commercial outcomes of serious games in companies: a review - Riedel, Johann Christian Karl Henry; Feng, Yanan; Azadegan, Aida; Romero, Margarida; Usart, Mireia; Baaslrud Hauge, Jannicke (Springer, 2014)
The objective of this paper is to review the work on the measurement of the commercial outcomes of serious games in companies and to provide a framework for their measurement in companies. The literature on the evaluation of training and in particular serious games is presented. A systematic literature review of studies of the impacts of business games in companies was undertaken. The paper summarises the existing studies on measuring the effectiveness of serious games in companies. A search of the grey literature was also conducted to establish what kinds of commercial outcomes have been measured and how. Finally, the paper presents some examples of measuring the commercial outcomes. It also provides some advice on how to measure commercial outcomes.